2007
DOI: 10.1093/ps/86.5.811
|View full text |Cite
|
Sign up to set email alerts
|

Development of Ascites-Resistant and Ascites-Susceptible Broiler Lines

Abstract: The rapid growth of modern broilers is associated with enhanced appetite and high metabolic rate and, consequently, high O(2) demand. Ascites syndrome (AS) develops in individuals that fail to fully supply the increasing demand for O(2) in their bodies under ascites-inducing conditions (AIC) such as high altitude or low temperatures. The tendency of broilers to develop AS is heritable, but efficacious selection against AS susceptibility (without affecting the normal expression of other important traits) requir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 27 publications
1
42
0
1
Order By: Relevance
“…Most broilers that remained healthy under the high-challenge AICs exhibited the same early GR and BW as those that later developed AS. These results, and the relatively high incidence of AS in the slow-growing line, indicated that there is very little, if any, direct genetic association between AS and genetic differences in potential GR, which suggests that AS-resistant broilers can be selected for higher GR These results, supported by several previous studies [68,[70][71][72][73][74][75][76][77][78], suggest that there is no "true" genetic correlation between the potential GR of broilers and their propensity to develop AS. It seems that AS is not caused by the increased O2 requirement of a fast growth rate, but by an impairment of the O2 supply needed to sustain the fast growth rate.…”
Section: Introductionsupporting
confidence: 78%
See 4 more Smart Citations
“…Most broilers that remained healthy under the high-challenge AICs exhibited the same early GR and BW as those that later developed AS. These results, and the relatively high incidence of AS in the slow-growing line, indicated that there is very little, if any, direct genetic association between AS and genetic differences in potential GR, which suggests that AS-resistant broilers can be selected for higher GR These results, supported by several previous studies [68,[70][71][72][73][74][75][76][77][78], suggest that there is no "true" genetic correlation between the potential GR of broilers and their propensity to develop AS. It seems that AS is not caused by the increased O2 requirement of a fast growth rate, but by an impairment of the O2 supply needed to sustain the fast growth rate.…”
Section: Introductionsupporting
confidence: 78%
“…Similarly successful divergent selection was applied by Druyan et al [70]: the 1st selection cycle was based on progeny testing for AS mortality under low-challenge AIC, and two further cycles of full-pedigree progeny testing were conducted under a high-challenge AIC protocol [70,72]. Two divergent lines were established: AS-susceptible (AS-S) and AS-resistant (AS-R), with, respectively, 95 and 5% AS incidence, i.e., a divergence of 90%, when reared together under the same high-challenge AIC [70].…”
Section: Direct Selection Against Susceptibility To Asmentioning
confidence: 99%
See 3 more Smart Citations